Electron beam induced current investigations of transition metal impurities at extended defects in silicon - Wilshaw, P; Fell, T (Electrochemical Soc Inc, 1995)
The electron beam induced current (EBIC) mode of a scanning electron microscopy is a useful technique for studying gettering of impurities to extended defects, its high sensitivity allowing very low impurity concentrations to be studied. Extended defects, when studied by EBIC, normally exhibit one of two different kinds of carrier recombination behavior. In the most common case this is accurately described by the Wilshaw model in which the recombination mechanism is charge controlled. Analyzed in terms of this physical model, quantitative EBIC experiments indicate that the small amount of recombination associated with deformation induced dislocations produced at 650°C or above and at stacking faults is due only to residual impurities, whereas a state intrinsic to the dislocation is produced by deformation at 420°C. There also exists a less common second type of recombination behavior, often associated with nickel contaminates, which can dominate at low temperatures. This type of recombination is less well understood and cannot be modeled by simple Shockley Read Hall recombination statistics.